Grammatical Coherence and Its Role in Achieving Text Cohesion: A Case Study in Some Texts of Bachir Al-lbrahimi’s Al-Athaar (Works) Athar - Belkacem, Djelikhi (LANGUAGE ART, 2022)
Textuality takes into account the global system that makes up a text, paying attention to both formal and semantic levels. Text linguistics recurs to both levels as a means for analysis that reveals text structure. The study of grammar interrelation is an essential step that aids in uncovering text structure and its cohesion, syntactically, semantically and in the diction choice as well. Grammar coherence is a pivotal component that contributed in making Al-lbrahimi’s texts feel coherent, unique and homogeneous.